Design and construction of a prototype to obtain gas hydrogen from waste water, and his application in the conservation of aguaymanto fruits (Physalis peruviana) - Garcia Escobar, Immer Mateo (2017)
The investigation was carried out in a period of 3 months in the company Karbel S.c.r.ltda L in the Huánuco region, having as general objective to evaluate the influence of different volumes of the hydrogen gas obtained with the prototype from wastewater, in the conservation of the Aguaymanto. The prototype was built using electronic circuits, transformers, Arduino, relays, glass jars, stainless   steel plates, etc. All of them were assembled; The stainless steel plates were placed in a glass jar, which has two energy inputs, which is supplied by a 15a transformer, controlled by an Arduino, relays and a Bluetooth port. By supplying the energy to the plates inside the vial in which the residual water is deposited, the hydrogen gas was obtained in an average amount of 305 cm3 per minute of operation. We evaluated 3 transformers of 10 A, 15a and 20a thus determining the optimal voltage, which is 15a by the low energy consumption. Hydrogen gas was applied to the Aguaymanto in 3 treatments: T1 = 400 cm3, T2 = 750 cm3 and T3 = 1100 cm3 at ambient temperature, which were compared with a sample witness to the same conditions. They were evaluated in two phases, the first phase constituted the first 15 days of the research, at this stage evaluated the organoleptic and physicochemical characteristics of the aguaymanto, obtaining as a result that treatments T1, T2 and T3 did not suffer Statistically significant changes, while the witness showed changes. The second phase was constituted the second 15 days of the research in which the treatments T1, T2 and T3 were evaluated. of which the treatment T1 showed a significant difference with respect to treatments T2 and T3. Concluding that the best treatment is T2 for the least energy consumption.